RUSSIAN-BELARUSIAN MULTICENTER GROUP STANDARD GUIDELINES FOR CHILDHOOD ACUTE LYMPHOBLASTIC LEUKEMIA FLOW CYTOMETRIC DIAGNOSTICS - I. A. Novikova; T. Yu. Verzhbitskaya; L. V. Movchan; G. A. Tsaur; М. V. Belevtsev; A. M. Popov (Онкогематология)
Background. Flow cytometry is one of the key technologies for acute lymphoblastic leukemia (ALL) diagnostics. Nevertheless lack of technological standards hampers implementation of immunophenotyping data in treatment protocols.Objective: development of harmonized guidelines for flow cytometric diagnostics of childhood ALL. Materials and methods. Three reference laboratories of the immunophenotyping group “Moscow–Berlin” took part in the development and standardization of approaches to the cytometric determination of the minimal residual disease. The sequence of steps for staining with monoclonal antibodies, selection of reagents for immunophenotyping, flow cytometer adjustment algorithms were discussed.Results. We developed and implemented in multicenter setting the harmonized approach for immunophenotyping flow cytometric childhood ALL. Successful integration of this protocol in the multicenter group has shown good level of our approach reproducibility. Conclusion. These results will allow implementing diagnostic standards in stratification system of pediatric ALL treatment protocols of russianbelarusian multicenter group.